Neuropathic Pain in Multiple Sclerosis and Its Animal Models: Focus on Mechanisms, Knowledge Gaps and Future Directions - Mirabelli, Ersilia; Elkabes, Stella (Frontiers in Neurology, 2021)
Multiple sclerosis (MS) is a multifaceted, complex and chronic neurological disease that leads to motor, sensory and cognitive deficits. MS symptoms are unpredictable and exceedingly variable. Pain is a frequent symptom of MS and manifests as nociceptive or neuropathic pain, even at early disease stages. Neuropathic pain is one of the most debilitating symptoms that reduces quality of life and interferes with daily activities, particularly because conventional pharmacotherapies do not adequately alleviate neuropathic pain. Despite advances, the mechanisms underlying neuropathic pain in MS remain elusive. The majority of the studies investigating the pathophysiology of MS-associated neuropathic pain have been performed in animal models that replicate some of the clinical and neuropathological features of MS. Experimental autoimmune encephalomyelitis (EAE) is one of the best-characterized and most commonly used animal models of MS. As in the case of individuals with MS, rodents affected by EAE manifest increased sensitivity to pain which can be assessed by well-established assays. Investigations on EAE provided valuable insights into the pathophysiology of neuropathic pain. Nevertheless, additional investigations are warranted to better understand the events that lead to the onset and maintenance of neuropathic pain in order to identify targets that can facilitate the development of more effective therapeutic interventions. The goal of the present review is to provide an overview of several mechanisms implicated in neuropathic pain in EAE by summarizing published reports. We discuss current knowledge gaps and future research directions, especially based on information obtained by use of other animal models of neuropathic pain such as nerve injury.